2018
DOI: 10.1113/ep086982
|View full text |Cite
|
Sign up to set email alerts
|

Motor cortical and corticospinal function differ during an isometric squat compared with isometric knee extension

Abstract: It has been suggested that task-specific changes in neurophysiological function (neuroplasticity) should be assessed using testing modalities that replicate the characteristics of the intervention. The squat is a commonly prescribed resistance exercise that has been shown to elicit changes in CNS function. However, previous studies have assessed squat-induced neuroplasticity using isometric knee extension, potentially confounding the results. The aim of the present study was to assess the agreement between cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
23
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 53 publications
4
23
0
1
Order By: Relevance
“…As is well established, MEPs are inherently variable due to the fluctuating nature of corticospinal and motoneuronal excitability (Ellaway et al., ; Kiers, Cros, Chiappa, & Fang, ), randomness in the firing of pyramidal tract neurons and spinal motoneurons (Pitcher, Ogston, & Miles, ) as well as desynchronisation of action potentials (Magistris, Rösler, Truffert, & Myers, ). The variability of responses observed in the present study is comparable to that reported previously when similar numbers of pulses were employed (Biabani, Farrell, Zoghi, Egan, & Jaberzadeh, ; Brownstein, Ansdell, Škarabot, Howatson, et al., ). A greater variability in MEPs compared to LEPs can perhaps be explained by differences in the complexity of the responses to TMS as opposed to LS as discussed above.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…As is well established, MEPs are inherently variable due to the fluctuating nature of corticospinal and motoneuronal excitability (Ellaway et al., ; Kiers, Cros, Chiappa, & Fang, ), randomness in the firing of pyramidal tract neurons and spinal motoneurons (Pitcher, Ogston, & Miles, ) as well as desynchronisation of action potentials (Magistris, Rösler, Truffert, & Myers, ). The variability of responses observed in the present study is comparable to that reported previously when similar numbers of pulses were employed (Biabani, Farrell, Zoghi, Egan, & Jaberzadeh, ; Brownstein, Ansdell, Škarabot, Howatson, et al., ). A greater variability in MEPs compared to LEPs can perhaps be explained by differences in the complexity of the responses to TMS as opposed to LS as discussed above.…”
Section: Discussionsupporting
confidence: 90%
“…The variability of evoked responses can be reduced by eliciting responses during a contraction (Darling, Wolf, & Butler, ), which is shown in the present data for both MEPs and LEPs. Due to inherent variability of evoked responses, a large quantity of evoked responses are recommended to ascertain a stable index of corticospinal excitability (Brownstein, Ansdell, Škarabot, Howatson, et al., ). The present data suggest that when using LS to evoke LEPs, fewer responses might be required compared to TMS evoked MEPs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This has also been observed earlier (e.g. Brownstein et al., 2018). Previous studies did not show a significant effect of caffeine on intracortical excitatory mechanisms (de Carvalho et al., 2010; Orth et al., 2005), but we cannot be sure that we were, in fact, testing this association owing to our inability to induce an average ratio of conditioned/unconditioned MEP amplitude >100%.…”
Section: Discussionsupporting
confidence: 86%
“…Subthreshold CS intensities of 60, 70, 80 and 90% AMT were applied. Inter-stimulus intervals of 2 (Brownstein et al 2018;Brownstein et al 2017;Goodall et al 2018) and 3 ms (O'Leary et al 2016;Thomas et al 2017b) for SICI and 10 (Di Lazzaro et al 2006;Volz et al 2012) and 15 ms (Chen et al 1998;Orth et al 2003) for ICF were examined at each CS intensity since these ISIs successfully elicited inhibition and facilitation in a number of previous studies. The order of conditions was pseudo-randomised and counterbalanced.…”
Section: Methodsmentioning
confidence: 99%